The effect of the lateral interactions on the critical behavior of long straight rigid rods on two-dimensional lattices - Longone, Pablo Jesus (2009)
Using Monte Carlo simulations and finite-size scaling analysis, the critical behavior of attractive rigid rods of length k (k-mers) on square lattices has been studied. An ordered state, with the majority of k-mers being horizontally or vertically aligned, was found. This ordered phase is separated from the disordered state by a continuous transition occurring at a critical density θc, which increases linearly with the magnitude of the lateral interactions.